2002
DOI: 10.3141/1787-09
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Testing of Suction and Deformation Properties of Base Course Aggregates

Abstract: The most significant problem related to base course aggregates in Finland and in many other countries affected by seasonal frost is the development of permanent deformations, especially during the frost-thawing period. From 1996 to 2000, a series of research projects was carried out to examine the mechanical, thermodynamic, electrical, and chemical factors that affect the seasonal variation of strength and deformation behavior of base course aggregates. The test series included frost heave tests and normal as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…Similar relationships ε p 1 ∼ q max /σ av 3 have been reported by several other researchers, e.g. [5][6][7]11,14,21,33,36,39,40,56,[61][62][63].…”
Section: Testing Program Of the Cyclic Triaxial Testssupporting
confidence: 88%
“…Similar relationships ε p 1 ∼ q max /σ av 3 have been reported by several other researchers, e.g. [5][6][7]11,14,21,33,36,39,40,56,[61][62][63].…”
Section: Testing Program Of the Cyclic Triaxial Testssupporting
confidence: 88%
“…In earth construction, it is generally known that the presence of fine particles between larger ones makes the compaction easier and increases density of the structure. The relation between fines content and permanent and resilient deformation properties is clearly shown in Kolisoja  et al ’s article 17. Concerning hardening, the work in real life with used loose-fill playground aggregates has revealed that in some cases material possesses a ‘cementing’ tendency where the particles adhere to each other forming a semihard crust on the top or to some distance below the surface of the shock-absorbing layer.…”
Section: Discussionmentioning
confidence: 96%
“…A series of research projects has been carried out in Finland and Texas where the relationship of the dielectric properties of Finnish and Texas base materials to their water content and strength and deformation properties was studied using a dynamic cone penetration (DCP) test, dynamic triaxial tests and a permanent deformation test (see Scullion, 1995, 1996;Kolisoja et al, 2002). A series of research projects has been carried out in Finland and Texas where the relationship of the dielectric properties of Finnish and Texas base materials to their water content and strength and deformation properties was studied using a dynamic cone penetration (DCP) test, dynamic triaxial tests and a permanent deformation test (see Scullion, 1995, 1996;Kolisoja et al, 2002).…”
Section: Unbound Pavement Structuresmentioning
confidence: 99%